A Dual Role by Incorporation of Magnesium in YbZn2Sb2 Zintl Phase for Enhanced Thermoelectric Performance. Issue 29 (24th June 2020) - Zhang, Zongwei; Yan, Yirui; Li, Xiaofang; Wang, Xinyu; Li, Juan; Chen, Chen; Cao, Feng; Sui, Jiehe; Lin, Xi; Liu, Xingjun; Xie, Guoqiang; Zhang, Qian
Abstract: 1‐2‐2‐type Zintl phase compounds have promising thermoelectric properties because of their complex crystal structures and multiple valence‐band structures. In this work, a series of single phase (Yb0.9 Mg0.1 )Mg x Zn2− x Sb2 ( x = 0, 0.2, 0.4, 0.6, 0.8, and 1) compounds are prepared by alloying YbZn2 Sb2 with 10 at% MgZn2 Sb2 and different amounts of YbMg2 Sb2 . The incorporation of Mg at the Yb site, as well as at the Zn site, not only leads to an effective orbital alignment confirmed by the dramatically enhanced density of states effective mass and Seebeck coefficients, but also increases the point defect scattering, contributing to a low lattice thermal conductivity ≈0.54 W m −1 K −1 at 773 K. Combined with the optimization of the carrier concentration by Ag doping at the Zn site, a highest ZT value ≈1.5 at 773 K is achieved in (Yb0.9 Mg0.1 )Mg0.8 Zn1.2 Ag0.002 Sb2, which is higher than that of all the previously reported 1‐2‐2‐type Zintl phase compounds. Abstract : YbZn2 Sb2 is alloyed with MgZn2 Sb2 and YbMg2 Sb2 to align the relevant orbitals and to decrease the lattice thermal conductivity. The carrier concentration is optimized by Ag doping and a maximum ZT of ≈1.5 at 773 K is achieved in (Yb0.9 Mg0.1 )Mg0.8 Zn1.2 Ag0.002 Sb2, which is higher than that of all the previously reported 1‐2‐2‐type Zintl phase compounds.